Thinking About Trauma: The Unique Contributions of Event Centrality and Posttraumatic Cognitions in Predicting PTSD and Posttraumatic Growth. Issue 6 (25th November 2013) - Barton, Sarah; Boals, Adriel; Knowles, Laura
<x xml:space="preserve">Abstract</x> Researchers have been investigating possible pathways to negative (posttraumatic stress disorder [PTSD]) and positive (posttraumatic growth [PTG]) reactions to trauma in recent decades. Two cognitive constructs, event centrality and posttraumatic cognitions, have been implicated to uniquely predict PTSD symptoms in an undergraduate sample. The current pair of studies attempted to (a) replicate this finding in an undergraduate sample, (b) replicate this finding in a treatment‐seeking sample, and (c) explore whether these 2 cognitive constructs uniquely predict PTG. The first study consisted of 500 undergraduate students, whereas the second study consisted of 53 treatment‐seeking clients. Results indicated both posttraumatic cognitions and event centrality uniquely predicted PTSD in the undergraduate (R2 = .46) and treatment‐seeking samples (R2 = .46). These 2 cognitive constructs also predicted PTG in the undergraduate sample (R2 = .37), but only posttraumatic cognitions predicted PTG in the treatment‐seeking sample (R2 = .17). The relationships between PTG varied, depending on whether PTG for high or low event‐centrality events were assessed. The original model was supported within both populations for PTSD symptoms, and its extension to PTG was supported within the treatment‐seeking sample. These results underscore cognitive and narrative factors in the progression of trauma.